Contemporary Cosmologies, Critical Reimaginings - Abramson, Allen (Religion and society, 2012)
How far is the ethnographic study of 'cosmologies' relevant to contemporary anthropology, and how might it illuminate understandings of the contemporary world? In this article we argue for a renewed anthropological interest in matters cosmological by seeking to disentangle the study of cosmology from the concomitants with which it was associated in earlier periods of anthropological research. In particular, we argue that an orientation toward cosmology continues to be of prime importance to the discipline insofar as it can be freed from its associations with holism and exoticism. The shift from 'high modernity' (in which orientations toward cosmos are variously constrained and circumscribed) to the flattening effects of the 'fluid' modernity of neoliberalism, we argue, has tended to thrust concerns with cosmic orders and dynamics back onto the forefront of people's lives. We end the article with a series of programmatic observations of how anthropologists might respond to these shifts, both ethnographically and analytically.